When it's good to have MAITs. Issue 10 (11th October 2020) - Souter, Michael NT; McCluskey, James; Corbett, Alexandra J
Abstract : This article discusses mucosal‐associated invariant T‐cell prophylactic and therapeutic vaccination schemes tested by Sakai et al . in mouse models of Mycobacterium tuberculosis infection together with the outcomes and observations.